2015
DOI: 10.1080/00927872.2014.934460
|View full text |Cite
|
Sign up to set email alerts
|

Involutions of a Clifford Algebra Induced by Involutions of Orthogonal Group in Characteristic 2

Abstract: Among the involutions of a Clifford algebra, those induced by the involutions of the orthogonal group are the most natural ones. In this work, several basic properties of these involutions, such as the relations between their invariants, their occurrences and their decompositions are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Such an involution is indecomposable if and only if it is either a 2-dimensional reflection or a 4-dimensional basic null involution (see [18,Theorem 1]). Some properties of 4-dimensional basic null involutions, called interchange isometries are investigated in [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an involution is indecomposable if and only if it is either a 2-dimensional reflection or a 4-dimensional basic null involution (see [18,Theorem 1]). Some properties of 4-dimensional basic null involutions, called interchange isometries are investigated in [13].…”
Section: Introductionmentioning
confidence: 99%
“…Every involution τ in O(V, q) induces a natural involution J τ , introduced by D. B. Shapiro [14], on the Clifford algebra C(q) satisfying J τ (v) = τ (v) for v ∈ V . In [11], it was shown that every totally decomposable algebra with involution over a field of characteristic different from 2 can be expressed as the Clifford algebra of a quadratic space with a natural involution induced by an involution in the orthogonal group (see [13] for a characteristic 2 counterpart). In characteristic 2, it is readily seen that the converse is also true (see (4.5)).…”
Section: Introductionmentioning
confidence: 99%